Dissecting Gender Bias: Critical Discourse Analysis of Advertisements in Indonesia - Rahmani, Irfa Luthfia; Meliana, Riska; Triyono, Sulis (Journal of Pragmatics and Discourse Research, 2024)
This research aims to identify gender equality issues by deconstructing the meaning of gender equality in advertisements from a feminist perspective through Critical Discourse Analysis. This research uses a descriptive qualitative research design with a Critical Discourse Analysis approach developed by Fairclough, which focuses on three main dimensions: textual dimension (microstructural), text production practice dimension (mesostructural), and socio-cultural practice dimension (macrostructural). Research data were obtained through interviews with informants as well as from advertisements related to gender equality aired on YouTube. Data collection techniques include interviews and the method of free listening and listening (SBLC) with note-taking techniques. The data collected was then analyzed using triangulation and deconstruction methods to reveal the ideology contained in the ad text and compare it with the informants' views. The results of this study show that societal norms often undermine women's abilities and limit women's roles to the domestic domain or as companions to their husbands. This research is expected to provide a deeper understanding of the meaning of gender equality in advertising media and help build a new perspective that is more inclusive and acceptable to society in Indonesia. The phenomenon of gender equality remains a challenge in many countries, including Pakistan and Nigeria, although the approaches and responses to this inequality differ in each country. In Pakistan, gender representations in media and advertising tend to reinforce traditional stereotypes, while in Nigeria, women are more active in fighting inequality through platforms such as blogs, which are used to criticize patriarchy and fight for social change. Deconstructing meaning in advertising allows researchers and academics to critically evaluate whether gender equality always places men in a dominant position over women, thus opening space for deeper analysis and more equitable solutions.